The Application of Photogrammetry in Audio-visual Art (on the Example of the Educational Professional Program “Advertising and Video Art” at KSADA) - Akerman, Oleksandr; Bedrina, Nadiia (HUDPROM: The Ukrainian Art and Design Journal, 2023)
Over the past few years, photogrammetry has attracted the attention of researchers worldwide in different aspects and branches of science. Ecological issues and environmental changes update research related to the digitisation and preservation of cultural heritage and museum exhibitions. Photogrammetric methods also find their place in video production – creating virtual doubles of people, buildings, or landscapes. This article brings up the question of the use of photogrammetric methods in the educational process at the educational professional program “Advertising and video Art” specialty 021 Audio-visual Art of the first degree of higher education at KSADA. Selected and detailed knowledge and skills obtained as a result of studying mandatory educational components (processing of static images, photography theory, work with video editors, compositing programs, colour theory, colour correction, grading, theory and practice of 3D modelling programs), which contribute to the study of the discipline of choice “Fundamentals of photogrammetry”. Following the analysis, the technology to create a photogrammetric project is considered step by step, the steps of this process are outlined and described, namely: the shooting process, processing of the captured material, creating a cloud of points, polygonization of the three-dimensional model, retopology of the model, texturing and texture baking. The main fields of application of the photogrammetry method in audio-visual art are identified: “practical” photogrammetry (digital conservation of architectural and sculpture monuments, copy of museum exhibitions); construction of models for further use in the production of films and videos; using photogrammetric models as objects of artistic creativity, including advertising; the use of unusual textures, perspectives, physical processes that cannot be implemented in the real world; creating large-scale copies of historic buildings and 3D printing sculptures.